PENGUATAN PERAN WARGA MASYARAKAT DALAM MITIGASI DAN ADAPTASI MENGHADAPI WABAH COVID-19 DI KABUPATEN BUTON TENGAH - Wa Ode Sitti Zubaydah; Nurramadhani A. Sida (Jurnal Pengabdian NUSANTARA, 2021)
In early 2020, Coronavirus Disease 2019 (COVID-19) was declared as a global pandemic by the World Health Organization (WHO). The number of positive cases of this virus continues to grow every day. Positive cases in Buton Tengah by 3 months increased up to 41 cases. Therefore the socialization of the mitigation and adaptation program of the people of Central of Buton during the COVID-19 outbreak needs to be done. The purpose is achievement of the ability to live a healthy life in the form of preventive measures to  faced covid-19 outbreak. Mitigation programs carried out are the Healthy Living Community Movement (GERMAS), clean and healthy living behavior (PHBS), Community Movement using masks (GEMAS), TOGA and VCO, as well as the use of handsanitizers and disinfectants. The method was discourse directly to the public. The results obtained is increased public understanding of how to prevent COVID-19 infection in the mitigation program delivered. Conclusion is the mitigation socialization of COVID-19 received a very good response from the community, the residents felt very helped and there was an increase in community understanding and skills.